MONTY PYTHON’S AND THE HOLY GRAIL: UMA ANÁLISE ESTÉTICA DO GROTESCO E SUA RELAÇÃO COM O RISO (REMUNOM, 2025)
We propose in this work to make an aesthetic appreciation of Monty Python's and the Holy Grail, with the intention of permeating the peculiarity of its cinematographic work, but also, through it, to think aesthetic categories of Brechtian universe and the critique of modernity proposed by Walter Benjamin. We want to distance ourselves from the vulgar common sense that exists in the mass reception of the cinematographic genre of comedy, to think how serious it can also be, in the specific rupture that the Pythonian cinematographic universe brings to the experience of mass reception. In this bias, the aesthetic universe of the cinematographic works of the Monty Python group works in the dramaturgical gears of nonsense, the grotesque, and the absurd. It provokes unusual laughter with its acid humor. It not only makes us laugh at what is external but also laugh at ourselves. In effect, this research contributes to studies on cinematographic language but specifically proves to be a work on the functioning of the psyche and the healing character of cinematographic work in modernity.